Predictors for urologic intervention and alternate diagnoses in people having computed tomography urography for suspected renal colic. (20th January 2016) - Blecher, Gabriel; Meek, Robert; Egerton‐Warburton, Diana; McCahy, Philip; Bach, Cindy; Boulos, Daniel
Abstract: Objective: The majority of ureteric calculi pass spontaneously and are uncomplicated, yet use of computed tomography urography (CTU) has increased in recent years. This study describes a cohort of ED patients undergoing CTU for renal colic and assesses the predictors of urologic intervention. Methods: A retrospective cohort study enrolled patients who underwent CTU at three Melbourne EDs. Demographic data, clinical assessments, laboratory and radiological findings and interventions were abstracted. Univariate analysis was performed and significant predictors were entered into a multivariate logistic regression model to calculate adjusted odds ratios for associations with urologic intervention. Results: Six hundred and seventeen patients underwent 626 CTUs; mean age was 48 and 67.7% were male. 58.2% of scans found calculi, of which median size was 4 mm. 9.2% of scans revealed an alternate diagnosis, of which 2.7% were acutely important. 14.6% of patients with calculi received an intervention. Multivariate analysis found the factors associated with intervention were female sex (OR 3.9, 95% CI 1.8–8.7), proximal calculus site (OR 4.1, 95% CI 1.5–11.7), single kidney (OR 9.0, 95% CI 1.7–49.0) and calculus size > 5 mm (OR 7.0, 95% CI 3.3–14.7). Conclusion: Factors associated with urologic intervention included female sex, single kidney, calculus size >5 mm and proximal calculus. Information on acute alternate diagnoses was uncommon. A prospective study is needed to further clarify clinical parameters that could predict intervention to allow targeting of CTU to those most likely to benefit.